¿Soy un "blawgger" o un abogado que da clases? - Bovino, Alberto (2011)
"In this work, we will use the terms commonly used in the blogosphere. The word 'blogosphere' designates the entirety of weblogs, blogs, or online journals on the Internet. In practice, it operates as a subnetwork within the Internet, due to the links formed between different blog circles. The term 'blagger,' on the other hand, designates legal bloggers. I must thank, as I do daily, my group of teaching assistants, without whom I wouldn't even be an AQDC anymore. They are the lawyers Edgardo Salatino, Tamara Tobal, Esteban Chervin, Cristian Penna, Maximiliano Medina, Luciana Pierbatistti, Josefina Minatta, Agustín Cavana, and Mauro Lopardo."-- The present work proposes to develop the use of the blogs in the area of the Law and the teaching. With this new tool of technology and of diffusion, the students have the space of taking an active role in the development of the classes of the curricula. Likewise, the field is opened for the debate and exchange of ideas, the present work does a tour for the blawgs most known about the legal world.